ANALISIS FAKTOR YANG BERHUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN PEDICULOSIS CAPITIS SISWA SEKOLAH DASAR NEGERI 2 KECAMATAN LASUSUA KABUPATEN KOLAKA UTARA - Widyastuti, Besse; Yusuf, Andi; Nur, Muh Ilyas (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
Head lice are small parasites found on the scalp and have the ability to suck blood from the head. Parasites, which in medical language are also called pediculosis capitis, This study aims to determine the factors related to personal hygiene and the incidence of pediculosis capitis in elementary school students in Lasusua District, North Kolaka Regency. This study uses a cross-sectional analytical method with a sample size of 60 students. Data analysis using the Che Square test shows that the results of the study show that there is a relationship between student knowledge (p value = 0.001), use of shared combs (p value = 0.000), frequency of washing hair (p value = 0.003), and gender (p value = 0.000) and the incidence of Pediculosis Capitis (head lice). Of the four variables studied, the use of shared combs was the most related factor to the spread of head lice among students.It is recommended that schools improve education about hygiene and the dangers of sharing personal items such as combs and introduce regular hair washing programs.